The Influence of Social Media Marketing and Brand Awareness on Purchase Decisions for Make Over Beauty Products - Salma Aulia Nur Rahman; Agus Aribowo (Sultan Publisher, 2024)
The purpose of this research is to determine whether or not Make Over beauty product sales are affected by social media marketing and consumer familiarity with the brand. Using a purposive sample methodology, 59 Gen Z respondents who had bought Make Over items were surveyed using Google Forms. Validity, reliability, multiple linear regression, t-test, F-test, and classical assumption test are some of the statistical tests used in this research, all conducted using SPSS 26. The findings demonstrated that compared to brand awareness, social media marketing significantly affects purchase choices. This finding is derived from the fact that brand awareness has a significant value of 0.112, which is higher than 0.05, and social media marketing has a significant value of 0.045, which is lower than 0.05. The significance of social media marketing tactics in the regional cosmetics sector is further explored in this research. If future studies want to get to the bottom of what factors influence consumers' choices to buy, they should use a bigger and more varied sample, according to this study's recommendations.